Facebook dan Pembelajaran Bahasa: Pengalaman Pembelajar dalam Belajar Tata Bahasa Inggris Menggunakan Grup Facebook - Wawa Puja Prabawa (Neolectura, 2022)
People feel that web 2.0 technologies and social networking sites (SNS), especially Facebook, are closely associated for use in educational programs as a learning tool, especially for the purpose of teaching and learning English. Rather, it has been seen as a way for students to supplement their formal education by conducting research and reading articles outside of the classroom. What I Like About Facebook, it can create a group learning, Dr. Grammar is the example. It is a Facebook group for learners who have desire to learn English grammar. This study explores Facebook and language learning in the context of learners’ experiences in learning English grammar using Dr. Grammar. Adopting a qualitative case study approach, it involved sixteen participants who enrolled Dr. Grammar through questionnaire and interview. Responses to Likerts-scale items were analyzed using percentage frequency response, while to yield a more in-depth analysis semi-structured interview was used to gain the participants’ responses. The results showed that learners experience positive attitude toward Facebook group in learning grammar through Dr. Grammar. This study suggests that learners must be able to not dependent on the teachers itself, they are allowed to learn and explore the use of technologies and social networking in fostering learners’ autonomous in the learning process.